The Level of Students Knowledge of Football Learning in The Covid-19 Era - Yunisal, Papat; Permana , Irpan (STKIP Paasundan Press, 2023)
This study aims to determine how big the level of students' knowledge of football learning in the covid-19 era. With this research, it is hoped that it can be seen the extent to which students are able to capture learning during this pandemic situation. This study uses a quantitative descriptive survey method with the distribution of digital questionnaires via google form. The subjects of this study were students majoring in TKJ SMK Pasundan 1 CImahi with a total of 50 people. The entire population was sampled so that in this study using total sampling, with a Guttman true-false test. Quantitative descriptive analysis technique as outlined in the percentage chart. The results showed that the level of students' knowledge of football learning in the covid-19 era was in the